Improving performance of polygenic risk scores for hypertension across two ancestry groups - Marguerite R. Irvin; Vinodh Srinivasasainagendra; Nicole D. Armstrong; Amit Patki; Ulrich Broeckel; Zhe Wang; Leslie A. Lange; Nita A. Limdi; Alicia Huerta-Chagoya; Joohyun Kim; Maggie C. Y. Ng; Josep M. Mercader; et al. (PLoS ONE, 2026)
Polygenic risk score (PRS) methods are evolving, and the benefit of adding functional annotations to the variant weights has been especially promising. However, less attention has been given to how the linkage disequilibrium (LD) reference panel used affects the score performance. In the current study, we compared two Bayesian approaches, one that incorporates functional annotations (LDpred-funct) and one that does not (PRS-CS), extending these applications to the hypertension (HTN) trait across two ancestry groups (European Americans EA, and African Americans, AA). In PRS-CS we used the standard HapMap 3 LD (HM3) reference panel, as well as a modified multi-ancestry reference panel (TagIt) with better coverage of variants from multiple ancestries. Individual-level data in 1,533 EA (58% with HTN) and 8,603 AA (71% with HTN) participants from the Reasons for Geographic and Racial Differences in Stroke Study (REGARDS) was used to optimize scores across the two approaches. PRS performance metrics including R 2 and odds ratios (OR) per standard deviation (SD) were then used to assess PRS performance in 1,270 EA (55% with HTN) and 1,896 AA (69% with HTN) participants from the Hypertension Genetic Epidemiology Network Study (HyperGEN). Among EAs in HyperGEN we observed an R 2 of 6.0% for LDpred-funct and R 2 of 7.3% for PRS-CS-TagIt versus R 2 of 1.4% for PRS-CS-HM3. The magnitude of the OR per SD for HTN was also higher for PRS-CS-TagIt OR=2.17 (95% CI 1.65–2.85, p = 3.0*10 −8 ) and LDpred-funct OR=2.14 (95% CI 1.61–2.85, p = 1.46*10 −7 ) versus PRS-CS-HM3 (OR=1.40; 95% CI 1.07–1.82, p = 1.19*10 −2 ). Among AAs in HyperGEN, the improvements were more modest, where we observed R 2 of 1.9% for LDpred-funct and R 2 of 2.9% for PRS-CS-TagIt versus 0.7% for PRS-CS-HM3. We found that both annotations and the updated LD panel improved the scores in both ancestry groups, but did not make the scores more equitable across the groups.